291Myocardial dysfunction in hypertrophic cardiomyopathy: primary effects of sarcomeric mutations versus secondary cardiomyocyte remodeling?. (15th July 2014) - Coppini, R; Gentile, F; Mazzoni, L; Ferrantini, C; Tosi, B; Ferrara, C; Tardiff, J; Tesi, C; Cerbai, E; Poggesi, C
Abstract: Introduction: In HCM human tissue, primary functional alterations at the level of the sarcomeres are associated with secondary changes of Ca2+ handling and membrane EP, leading to a pro-arrhythmogenic phenotype and alteration of myocardial relaxation (Circulation. 2013 Feb 5;127(5):575-84). The relative contribution of primary vs secondary alterations is still unknown. Methods: Here we aim to study these changes in intact trabeculae, single cardiomyocytes and skinned preparations from the ventricles of transgenic mouse models aged 6 months carrying HCM-related mutations of cTnT (R92Q, E163R). Results: Compared to WT, R92Q trabeculae showed: (i) preserved peak isometric twitch tension at low inotropic level with reduced contractile reserve; (ii) prolonged relaxation kinetics associated with reduced SERCA function; (iii) faster mechanical restitution, indicating shorter RyR2 refractoriness; (iv) Frequent after-contractions or spontaneous beats during pauses, which increased in response to isoproterenol. Compared to WT, R92Q cardiomyocytes showed: (i) prolonged action potentials due to ionic current remodeling; (ii) reduced amplitude and slower decay rate of Ca2+transients; (iii) elevated diastolic [Ca2+]I and (iv) spontaneous Ca2+ waves and Ca2+transients under isoproterenol. In E163R vs. WT trabeculae and cells, peak isometric tension and Ca2+ transient amplitude were preserved in all conditions. Interestingly, the kinetics of force development and relaxation was prolonged, despite Ca2+ transient kinetics was faster and SERCA function unchanged. E163R myocardium showed faster mechanical restitution and increased spontaneous activity. Further, E163R myofibrils showed a prolongation of the overall relaxation, with incomplete inactivation in the absence of Ca2+. Energy cost of contraction, measured with an enzymatic assay of sarcomeric ATPase activity, as well as myofilaments Ca2+ sensitivity, were increased in E163R vs. WT skinned trabeculae. Conclusions: Primary changes of myofilaments function (increased Ca2+ sensitivity), previously described in R92Q hearts, are associated with a large spectrum of EC-coupling and membrane EP changes, which appear to be a major contributor to the observed mechanical dysfunction and arrhythmogeneicity in this mouse line, resembling advanced human disease. In E163R instead, impairment of myofilament function appear to be the leading element determining mechanical abnormalities. In the absence of major EC-coupling changes, the increased arrhythmogeneicity in E163R myocardium may be a direct consequence of the increased myofilaments Ca2 sensitivity.